Phylogenetic relationships of Malaysian monkeys, Cercopithecidae, based on mitochondrial cytochrome c sequences - Md-Zain, B.M.; Mohamad, M.; Ernie-Muneerah, M.A.; Ampeng, A.; Jasmi, A.; Lakim, M.; Mahani, M.C. (Genetics and Molecular Research, 2010)
Mitochondrial DNA cytochrome c oxidase II (COII) gene sequences of Malaysian Cercopithecidae were examined to ascertain their phylogenetic relationships. Colobinae were represented by the genera Presbytis, Trachypithecus and Nasalis, while the genus Macaca represented Cercopithecinae. DNA amplification and sequencing of the COII gene was performed on 16 samples. Symphalangus syndactylus (Hylobatidae) was used as the outgroup. Data were analyzed using both character (maximum parsimony) and distance (neighbor-joining) methods. Tree topologies indicated that Colobinae and Cercopithecinae have their own distinct monophyletic clade. This result was well supported by bootstrap values and genetic distances derived from the Kimura-2-parameter algorithm. Separation of Macaca nemestrina from M. fascicularis was also well supported by bootstrap values. In addition, tree topologies indicate a good resolution of the Colobinae phylogenetic relationships at the intergeneric level, but with low bootstrap support. The position of Nasalis remained problematic in both trees. Overall, COII is a good gene candidate for portraying the phylogenetic relationships of Malaysian primates at the inter- and intra-subfamily levels.